2018
DOI: 10.1186/s12917-018-1410-7
|View full text |Cite
|
Sign up to set email alerts
|

Computer simulation of syringomyelia in dogs

Abstract: BackgroundSyringomyelia is a pathological condition in which fluid-filled cavities (syringes) form and expand in the spinal cord. Syringomyelia is often linked with obstruction of the craniocervical junction and a Chiari malformation, which is similar in both humans and animals. Some brachycephalic toy breed dogs such as Cavalier King Charles Spaniels (CKCS) are particularly predisposed. The exact mechanism of the formation of syringomyelia is undetermined and consequently with the lack of clinical explanation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 66 publications
3
14
0
Order By: Relevance
“…Although these results demonstrate an association only, the possibility that there is a causal relationship between TL SM and location of the termination of the dural sac deserves investigation. These findings corroborate a recent 3‐dimensional computer modeling study that suggested cord tethering might be involved in SM development in the canine spinal cord . There remains a need to investigate whether the caudal location of the spinal cord termination in CKCS simply represents the relative lengths of the spinal cord and vertebral column in this breed or is the result of tethering, and if so, whether tethering contributes to the development of SM.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Although these results demonstrate an association only, the possibility that there is a causal relationship between TL SM and location of the termination of the dural sac deserves investigation. These findings corroborate a recent 3‐dimensional computer modeling study that suggested cord tethering might be involved in SM development in the canine spinal cord . There remains a need to investigate whether the caudal location of the spinal cord termination in CKCS simply represents the relative lengths of the spinal cord and vertebral column in this breed or is the result of tethering, and if so, whether tethering contributes to the development of SM.…”
Section: Discussionsupporting
confidence: 86%
“…While initial veterinary research on CMSM focused on skull and brain morphology, the importance of the craniocervical junction morphology became clearer over time, leading some authors to rename the disorder craniocervical junctional disorder . The possibility that there is also a mismatch between the vertebral column and spinal cord length is now being investigated by us and others . In light of this, given there may be differences in vertebral column and spinal cord relationships between breeds with different skull shapes, we subdivided control dogs into brachycephalic and mesaticephalic breeds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pilot studies in this technology has identified biomarkers in structures such as the soft palate not previously associated with these conditions that when investigated may give further insight into conformation change. Mathematical modeling has also been applied to the dynamics associated with CSF flow which might be used to predict the outcome following different surgical approaches ( 151 ). The challenge of quantifying and interpreting intermittent and variable clinical signs for a complex trait such as CM/SM cannot be overstated.…”
Section: Conclusion and Future Developmentsmentioning
confidence: 99%